IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA KONSEP PENCEMARAN LINGKUNGAN DI KELAS X SMA NEGERI 2 KUNINGAN - Melinda Meliyasari; Anna Fitri Hindriana; Haruji Satianugraha (Quagga : Jurnal Pendidikan dan Biologi, 2015)
This study aims to determine how the creative thinking abilities of students through the application of learning models of type group cooperative investigation of the students' creative thinking ability. Creative thinking abilities of students used in this study include three indicators of the ability to think flexibly (flexibility), original thinking skills and the ability to think elaborative. This research was conducted at SMAN 2 Kuningan. The method used in this study is an experimental method to design queasy experiment with pre-post test control group. Population taken in this study were all tenth grade students at SMAN 2 Kuningan school in Academic year 2012/2013 a total of seven classes with the number 288 students. Technique sampling by cluster random sampling in 2 to each class there are 32 students in the experimental class and 32 students for grade control data processing technique used is normality test, homogeneity, and hypothesis testing (t test). Based on the test results obtained by statistical hypothesis test value t hit (3.25) t daf (1.67), then thank Hi means that t hits (4.410) t daf (1.67), then the received meaning Hi there implementation of cooperative learning model group investigation can improve students' ability to think creatively on the concept of environmental pollution in tenth grade students at SMA Negeri 2 Kuningan. From these results it can be concluded that the application of cooperative learning model group investigation may improve the ability to think creatively, it is indicated from the value of post test students' ability to think creatively experimental class better than the control class. Key Keyword : Group Investigation, Thinking creative ability; flexibility thinking, original thinking, elaborative thinking.